Wage Dispersion and Overqualification as Entailed by Reder Competition - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
The expansion of higher education in the Western countries has been accompanied by a marked widening of wage differentials and increasing overqualification. While the increase in wage differentials has been attributed to skill-biased technological change that made advanced skills scarce, this explanation does not fit well with the observed increase in overqualification which suggests that advanced skills are in excess supply. By "Reder-competition" I refer to the simultaneous adjustment of wage offers and hiring standards in response to changing labor market condition. I present a simple model of Reder competition that reproduces the simultaneous increase in wage differentials and overqualification in response to an increase in education.
urn:nbn:de:bvb:19-epub-1976-1
Keywords: J31; J63; D43; 330; Hiring standards; employment criteria; selection wages; efficiency wages; mobility; skill-biased technical change; overeducation; wage dispersion; Reder competition; Personalbeschaffung; Qualifikation; Lohnstruktur; Unterbeschäftigung; Technischer Fortschritt